If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.66p = 49 + -1x Solving 0.66p = 49 + -1x Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '0.66'. p = 74.24242424 + -1.515151515x Simplifying p = 74.24242424 + -1.515151515x
| -4x+3-x=-3(x+1) | | x^2-2x-54=9 | | Y=ln(6+x^2) | | 653=4x+2y | | t(8-3)=10 | | 24=3(jk-5) | | 5r-8(r+6)=22+7r | | 5x/.12=15 | | 15x^2+22=-8 | | 16w^2-40w+25=0 | | 9+9v=-54 | | 4ln(x)=ln(27x) | | A=1/2(xh-yh) | | 3-6+1=-2x-5+5x | | 4x+1=9x-7 | | -7-n=-17 | | 5t+16=8t-2 | | 2x+3x+2=10 | | -5(2f+4)=-10 | | .33(21-3a)=6-a | | 5x-6=14-3x | | 15+3x=25 | | 5(f-4)=0 | | 6x+9=-4x-1 | | 5(11w+1)= | | 10+9x=181 | | 10(s-4)=-113 | | -78=7+5n | | -76=2+6a | | slope=1/5:(2,-6) | | (6x+10)(x+2)= | | 2x^3+2x^2-8x-12=0 |